PENGARUH KEPEMIMPINAN TRANSFORMATIONAL KEPALA SEKOLAH TERHADAP PENINGKATAN KOMPETENSI GURU DAN KINERJA TENAGA KEPENDIDIKAN DI SEKOLAH ISLAM AL-IZHAR CENDEKIA MAKASSAR - Nurhalisa, Sitti; Ansar; Arnidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Improving the quality of educational services in the digital era presents a significant challenge, especially for schools grounded in Islamic values such as Sekolah Islam Al-Izhar Cendekia Makassar. School principals are expected to adopt leadership styles that promote innovation, teacher professionalism, and the effectiveness of educational staff performance. This study aims to examine: (1) the influence of the principal’s transformational leadership on teacher competence; (2) the influence of transformational leadership on the performance of educational staff; and (3) the simultaneous influence of transformational leadership on both teacher competence and staff performance. This research is a quantitative study with an associative approach, conducted at Sekolah Islam Al-Izhar Cendekia Makassar. The population consisted of all teachers and educational staff, totaling 50 people, with a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using SPSS 27. The results show that the school principal's transformational leadership has a positive and significant influence on teacher competence (49%), on staff performance (50.2%), and simultaneously contributes to improving the quality of educational services. In conclusion, transformational leadership is effective in creating a professional and conducive work environment in Islamic schools.